2013
DOI: 10.1007/s00109-013-0992-6
|View full text |Cite
|
Sign up to set email alerts
|

Stable tumor vessel normalization with pO2 increase and endothelial PTEN activation by inositol trispyrophosphate brings novel tumor treatment

Abstract: Tumor hypoxia is a characteristic of cancer cell growth and invasion, promoting angiogenesis, which facilitates metastasis. Oxygen delivery remains impaired because tumor vessels are anarchic and leaky, contributing to tumor cell dissemination. Counteracting hypoxia by normalizing tumor vessels in order to improve drug and radio therapy efficacy and avoid cancer stem-like cell selection is a highly challenging issue. We show here that inositol trispyrophosphate (ITPP) treatment stably increases oxygen tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
153
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(157 citation statements)
references
References 47 publications
3
153
1
Order By: Relevance
“…ITPP had no effect on U87 cell proliferation in vitro. In another study by Kieda et al, it was described that ITPP treatment reduced the size of malignant melanomas in mice and reduced the metastatic invasion, leading to increased survival compared to control animals (2).…”
Section: Abstract Background: Inositol Trispyrophosphate (Itpp) Has mentioning
confidence: 96%
See 4 more Smart Citations
“…ITPP had no effect on U87 cell proliferation in vitro. In another study by Kieda et al, it was described that ITPP treatment reduced the size of malignant melanomas in mice and reduced the metastatic invasion, leading to increased survival compared to control animals (2).…”
Section: Abstract Background: Inositol Trispyrophosphate (Itpp) Has mentioning
confidence: 96%
“…These vessels are permeable and allow tumour spreading. The driving force is thought to be the hypoxic state created by the tumour itself (2). It has been shown that inositol trispyrophosphate (ITPP) treatment increases oxygen delivery to the tumour and reduces tumour growth, thus resulting in a more favourable outcome in animal models with pancreatic cancer (3), liver cancer (4) and glioblastoma cells implanted on membranes (5).…”
Section: Abstract Background: Inositol Trispyrophosphate (Itpp) Has mentioning
confidence: 99%
See 3 more Smart Citations